Suspension copolymerization of styrene/divinylbenzene with gel formation: kinetic modelling using in-line FTIR-ATR monitoring and SEC-MALLS product characterization - Gonçalves, Miguel A.D. (2010)
Experimental and theoretical studies concerning the suspension copolymerization of styrene with divinylbenzene are reported. Experiments are carried out in a batch stirred reactor, at 1.2 dm3 scale, and extended beyond gelation in order to synthesize macroporous copolymer networks with applications for many separation processes